2015
DOI: 10.12944/cwe.10.3.23
|View full text |Cite
|
Sign up to set email alerts
|

Rainfall Stability and Drought Valuation (Using Spi) Over Southern Zone of Tamil Nadu

Abstract: Drought is the most extensive hydro-meteorological pattern of prolonged period of water scarcity affecting natural resources and environment. However, it has significantly different characteristics from one region to another. Tamil Nadu agonizes from various disasters including droughts. Generally rainfall deviation from the long-term mean continues to be a widely adopted indicator for drought intensity assessment. The application of this indicator is strongly limited by its inherent nature of its dependence o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 10 publications
1
1
0
Order By: Relevance
“…Thus, the SPI and rainfall deviation from the mean shows the same observation which signifies a strong interrelationship between these two parameters. Previous studies also reported a similar observation for the variability of monsoons across the study area [17,37]. The seasonal SPI also showed a comparatively higher drought events during the North East Monsoon.…”
Section: Drought Frequency and Intensity Analysis From Standardized P...supporting
confidence: 85%
See 1 more Smart Citation
“…Thus, the SPI and rainfall deviation from the mean shows the same observation which signifies a strong interrelationship between these two parameters. Previous studies also reported a similar observation for the variability of monsoons across the study area [17,37]. The seasonal SPI also showed a comparatively higher drought events during the North East Monsoon.…”
Section: Drought Frequency and Intensity Analysis From Standardized P...supporting
confidence: 85%
“…As a result, drought risk assessment is required to deal with this terrible drought, which has a significant impact on society. Because they simplify complicated inter-relationships between various climatic factors, drought indices are among the most significant instruments for monitoring and assessing drought [17]. Guhathakurta [18] evaluated the risk of districtwide droughts across India using PNP from the southwest monsoon season (June to September) for 424 districts over 14 years (1988-2001) and found the highest chance (>60 percent) in various districts in northern India.…”
Section: Drought Is Further Classified Into Different Categories: I) ...mentioning
confidence: 99%